Positive welfare effects of trade barriers in a dynamic equilibrium model - Jan Tuinstra; Michael Wegener; Frank Westerhoff (Bamberg University, Bamberg Economic Research Group (BERG), 2013)
We develop a simple two-region, cobweb-type dynamic equilibrium model to demonstrate the existence of optimal trade barriers. A pure comparative statics analysis of our model suggests that a reduction of trade barriers always enhances welfare. However, taking a dynamic perspective reveals that nonlinear trade interactions between the two regions may generate endogenous price fluctuations which can hamper both consumer and producer surplus. Finally, we allow special interest groups, such as consumers or producers from the two regions, to lobby for a particular level of trade barriers. Our model predicts that time-varying trade barriers may be another channel for market instability.
Keywords: D72; F13; H21; 330; cobweb dynamics; market interactions; optimal import tariffs; welfare analysis; political economy of trade barriers